2004
DOI: 10.1029/2003jb002816
|View full text |Cite
|
Sign up to set email alerts
|

A model of deep crustal fluid flow following the Mw = 8.0 Antofagasta, Chile, earthquake

Abstract: [1] We develop a model to test the hypothesis that a high fluid pressure pulse and subsequent fluid flow caused a spatially extensive increase in the V P /V S ratio following the M w = 8.0 Antofagasta, Chile, subduction zone earthquake. The postseismic anomaly appeared within a 50-day period inside the forearc region of the Andes continental crust. We model this anomaly with a poroelastic medium that combines the fluid flow response to mean stress changes from slip along a dislocation plane, with a pore pressu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
31
0

Year Published

2005
2005
2022
2022

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(34 citation statements)
references
References 56 publications
(99 reference statements)
3
31
0
Order By: Relevance
“…The ratio V p / V s is a quantity frequently used in seismology and V p / V s anomalies have sometimes been recorded before and after earthquakes. For example, after the Antofagasta earthquake, an anomaly of V p / V s was observed [ Husen and Kissling , 2001; Koerner et al , 2004]: V p / V s increased from 1.72 to a significant mean value of 1.77. Husen and Kissling [2001] suggested that the anomaly was fluid driven.…”
Section: Discussionmentioning
confidence: 99%
“…The ratio V p / V s is a quantity frequently used in seismology and V p / V s anomalies have sometimes been recorded before and after earthquakes. For example, after the Antofagasta earthquake, an anomaly of V p / V s was observed [ Husen and Kissling , 2001; Koerner et al , 2004]: V p / V s increased from 1.72 to a significant mean value of 1.77. Husen and Kissling [2001] suggested that the anomaly was fluid driven.…”
Section: Discussionmentioning
confidence: 99%
“…Besides bulk viscoelastic processes, poroelastic processes have also been inferred as a primary source of postseismic deformation for shallow strike‐slip earthquakes [e.g., Peltzer et al , 1996; Jónsson et al , 2003]. Subsurface fluid flow following the 1995 earthquake is suggested based on independent evidence [ Husen and Kissling , 2001; Koerner et al , 2004] and may also contribute to postseismic deformation. A simple calculation for northern Chile (using plausible values for the drained and undrained Poisson's ratio [ Rice and Cleary , 1976]) indicates that the direction of deformation is opposite that observed and the amplitude is probably an order of magnitude too small [ Pritchard , 2003].…”
Section: Modeling Strategymentioning
confidence: 99%
“…Besides for borehole fluid injections, pore pressure diffusion (described by either the coupled or uncoupled equations) as triggering mechanism has been proposed for various case studies: e.g., for reservoir (large artificial lakes) induced seismicity [ Howells , 1974; Talwani , 2000], for water table changes in large basins connected with microseismicity [ Costain and Bollinger , 1991; Lee and Wolf , 1998], for volcanic seismicity in Italy [ Saccorotti et al , 2002], and for aftershocks of large earthquakes [ Nur and Booker , 1972; Bosl and Nur , 2002; Jonsson et al , 2003; Shapiro et al , 2003; Miller et al , 2004; Koerner et al , 2004]. …”
Section: Triggering Mechanism Of Pore Pressure Diffusionmentioning
confidence: 99%